2013
DOI: 10.1590/s0100-06832013000500029
|View full text |Cite
|
Sign up to set email alerts
|

Doses de lodo de esgoto compostado em produção de tapete de grama esmeralda imperial

Abstract: RESUMO A eficiência da adubação nitrogenada para gramados pode ser aumentada com a utilização de fontes de liberação lenta, como composto de lodo de esgoto, que, em razão das suas características, pode ser um substituto de parte ou do total da adubação inorgânica para as gramas. Não foram encontrados resultados referentes à utilização de lodo compostado na cultura da grama, no Brasil. Objetivou-se com este trabalho avaliar o efeito de doses de composto de lodo de esgoto na produção da grama esmeralda Imperial.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…The most important variation was Zn, which was present at a high concentration in CSS (Table 2). Backes et al [41] found that increasing CSS rates from 0 to 48 Mg ha −1 on a Rhodic Hapludox, as was investigated in this study, but cultivated with zoysia grass (Zoysia japonica Steud. ), resulted in an increase in (bio)available Zn concentrations in soil.…”
Section: 1mentioning
confidence: 54%
“…The most important variation was Zn, which was present at a high concentration in CSS (Table 2). Backes et al [41] found that increasing CSS rates from 0 to 48 Mg ha −1 on a Rhodic Hapludox, as was investigated in this study, but cultivated with zoysia grass (Zoysia japonica Steud. ), resulted in an increase in (bio)available Zn concentrations in soil.…”
Section: 1mentioning
confidence: 54%
“…Plots that received syntetic fertilization (SF) showed a SCR of approximately 21%, 12%, 10% and 29% lower in comparison to the highest dose of applied sludge. Backes et al (2013), comparing a dose of 48 Mg ha -1 of sludge with a control (no fertilization), showed a lower SCR by 61% and 65% at 45 and 130 DAA, respectively.…”
Section: Resultsmentioning
confidence: 91%
“…The amount of time may not have been sufficient to release all nutrients. According to the nutrient evaluation conducted by Backes et al (2013), 67% of the N is released within a period of up to 120 days. Meanwhile, Godoy et al (2007) note the need for basic fertilization for shoot development to begin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Backes et al (2013) obtained maximum sod resistance with the estimated composted sewage sludge dose of 46.9 Mg ha −1 (corresponding to approximately 469 kg ha −1 N).…”
Section: Dry Biomass and Macronutrient Accumulation In Leaves + Stemsmentioning
confidence: 85%